The Effect of Cooling Rate after Homogenization on the Microstructure and Properties of 2017a Alloy Billets for Extrusion with Solution Heat Treatment on the Press - Woźnicki A. (Archives of Metallurgy and Materials, 2016)
The influence of cooling rate after homogenization on the 2017A alloy microstructure was analysed. The capability of the θ (Al2Cu) particles, precipitated during various homogenization coolings, for rapid dissolution was estimated. For this purpose, the DSC test was used to determine the effect of the cooling rate after homogenization on the course of melting during a rapid heating. Moreover, the samples after solution heat treatment (with short time annealing) and ageing, were subjected to the microstructure investigations and the microhardness of grains interiors measurements. It was found that cooling after homogenization at 160 °C/h is sufficient for precipitation of fine θ phase particles, which dissolve during the subsequent rapid heating. The cooling at 40 °C/h, causes the precipitation of θ phase in the form of large particles, incapable of further fast dissolution.